HUBUNGAN FAKTOR INDIVIDU DAN LINGKUNGAN DENGAN KEJADIAN MALARIADI WILAYAH KERJA PUSKESMAS SEKURA KABUPATEN SAMBAS PROVINSI KALIMANTAN BARAT - , SELVIANA, Prof. Dr. dr. Soeyoko, DTM & HSU ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Malaria has been endemical in the area of Public Health Center Sekura, Sambas. The increasing of Annual Parasite Incidence (API) in 2009 was around 4.31 per mile, and then increased to 4,42 per mile in 2010, before finally increased to 5,93 per mile in 2011. Therefore, in 2011 the work area of Public Health Center Sekura was classified as endemic area of malaria with the High Incidence Area status. Objective: To determine the relationship among individual and environmental factors with the malaria occurrences. To map the spatial distribution of malaria cases and the habitat for Anopheles Sp to breed its larva spatially in the work area of Public Health Center Sekura, Sambas West Borneo. Research Method: Observational research using case control design through Geographic Information System (GIS). Sample was counted using hypothesis odds-ratio test formula. There were 58 respondents as sample group and 58 respondents as control group. Analysis was done through bivariate analysis, multivariate analysis, and spatial. Result: Bivariate analysis in the work area of Public Health Center Sekura showed: relationship of the use of mosquito net (p = 0,000